CSPα promotes SNARE-complex assembly by chaperoning SNAP-25 during synaptic activity - Sharma, Manu; Burré, Jacqueline; Südhof, Thomas C. (Nature cell biology, 2011)
A chaperone complex containing CSPα, Hsc70 and SGT binds to monomeric SNAP-25 and prevents its aggregation and degradation. Loss of CSPα inhibits SNARE complex formation. A neuron forms thousands of presynaptic nerve terminals on its axons, far removed from the cell body. The protein CSPα resides in presynaptic terminals, where it forms a chaperone complex with Hsc70 and SGT. Deletion of CSPα results in massive neurodegeneration that impairs survival in mice and flies. In CSPα -knockout mice, levels of presynaptic SNARE complexes and the SNARE protein SNAP-25 are reduced, suggesting that CSPα may chaperone SNARE proteins, which catalyse synaptic vesicle fusion. Here, we show that the CSPα–Hsc70–SGT complex binds directly to monomeric SNAP-25 to prevent its aggregation, enabling SNARE-complex formation. Deletion of CSPα produces an abnormal SNAP-25 conformer that inhibits SNARE-complex formation, and is subject to ubiquitylation and proteasomal degradation. Even in wild-type mouse terminals, SNAP-25 degradation is regulated by synaptic activity; this degradation is decreased by CSPα overexpression, and enhanced by CSPα deletion. Thus, SNAP-25 function is maintained during rapid SNARE cycles by equilibrium between CSPα-dependent chaperoning and ubiquitin-dependent degradation, revealing unique protein quality-control machinery within the presynaptic compartment.